The Relationship between Work and Maternal Knowledge with Exclusive Breastfeeding in the Working Area of the Health Center - Suciati, Indah; Wahyuni, Sari; Aprilina, Aprilina (Journal of Maternal and Child Health Sciences (JMCHS), 2025)
Exclusive breastfeeding is an important effort to improve the health and development of babies, which is encouraged by various health organizations throughout the world. However, the rate of exclusive breastfeeding still varies significantly in different regions, which can be influenced by various factors. The study aim to explore the relationship between mother's work and knowledge and exclusive breastfeeding practices. This research is analytical observational. This research was conducted in May 2024 in the L Sidoharjo Health Center Work Area with a population of 152 mothers with babies 7-12 months and a sample of 35 mothers with babies 7-12 months. Data analysis using Chi-Square. The results showed that working mothers did not provide exclusive breastfeeding (87,5%) and non-working mothers provided exclusive breastfeeding (81,5%) with p=0.000. The research results show that there is an influence of work on exclusive breastfeeding. Good knowledge provides exclusive breastfeeding (77.8%) with p=0.006. The research results show that there is an influence of knowledge on exclusive breastfeeding. It can be concluded that, there is an influence of work and knowledge on exclusive breastfeeding.